Osteoporosis - From a Constitution Fed by Causa Occasionalis (Homoeopathy for All, 2023)
What exercise can do to our body,  becomes all the more important  in winters, when the cozy cover  of warm quilt pushes us towards  insidiously injurious sedentary  lifestyle (causa occasionalis)  which escalate propensity towards  gruesome health conditions  (constitutional dyscrasias). WHO warns that sedentary  lifestyle is a harbinger of various  causes of mortality, ushering the  ignorant human to a multitude  of lifestyle disorders like  cardiovascular diseases, diabetes,  obesity etc. and heighten the risk of  colon cancer, high blood pressure,  osteoporosis, lipid disorders,  depression and anxiety. According  to WHO, 60 to 85% of the world  population from both developed as  well as developing countries lead  sedentary lifestyle. Estimates show  that nearly two-third of children  are also insufficiently active, which  poses serious questions on their  future health outcomes.1
Keywords: winters; lipid; countries; health